On Prevention of Diarrheal Disease: Assessing the Factors of Effective Handwashing Facilities in Bangladesh - Hossain, Sorif; Islam, Md. Mazharul; Khokon, Md. Asraful Islam; Islam, Md. Monirul (Journal of Population and Social Studies [JPSS], 2021)
People in Bangladesh usually do not utilize handwashing facilities properly, which makes it challenging to implement hygiene practices of handwashing to reduce diarrhea and other health risks. Against this backdrop, this research attempts to assess the factors associated with Effective Handwashing Facilities (EHFs) in Bangladesh utilizing the Multiple Indicator Cluster Survey 2019. This study utilizes descriptive statistics techniques and also bivariate and multivariable logistic regression methods by representing odd ratios to identify the relationship between associated factors and EHF in Bangladesh. The descriptive statistics show that about 74.22% of the households in Bangladesh have EHFs. Gender, education, ethnicity, male-head households, household wealth status, source of water, sanitation status, sharing toilet facility are identified as the potential determinants of EHF. As a result, we recommend that all levels of society in Bangladesh have continuous access to handwashing equipment and facilities to reduce hygiene-related illnesses especially diarrheal disease.